Pengaruh Hedonic Shopping Motivation dan Shopping Lifesytle Terhadap Impulse Buying Melalui Positive Emotion - Rabbani, M Rizki; Wijayanto, Gatot; Novrianti, Dian Puspita (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aims to analyze the effect of Hedonic Shopping Motivation and Shopping Lifestyle on Impulse Buying through Positive Emotion on H&M consumers in Pekanbaru. The data collection technique in this research is literature study and questionnaires. The population in this study were H&M consumers in Pekanbaru. The number of samples taken in this study were 384 samples. The sampling method used in this study is non-probability sampling using the accidental sampling technique. The data processed using the SEM-PLS method with SmartPLS 3.0 software. The results of this study indicate that Hedonic Shopping Motivation has an effect on Positive Emotion, Shopping Lifestyle has an effect on Positive Emotion, Positive Emotion has an effect on Impulse Buying, Hedonic Shopping Motivation has no effect on Impulse Buying, Shopping Lifestyle has an effect on Impulse Buying, Hedonic Shopping Motivation affects Impulse Buying through Positive Emotion, and Shopping Lifestyle affects Impulse Buying through Positive Emotion. Abstrak Penelitian ini bertujuan untuk menganalisis pengaruh Hedonic Shopping Motivation dan Shopping Lifestyle terhadap Impulse Buying melalui Positive Emotion pada konsumen H&M di Pekanbaru. Teknik pengumpulan data dalam penelitian ini adalah studi pustaka dan kuesioner. Populasi dalam penelitian ini adalah konsumen H&M di Pekanbaru. Jumlah sampel yang diambil dalam penelitian adalah 384 sampel. Metode pengambilan sampel yang digunakan dalam penelitian ini adalah non-probability sampling dengan menggunakan teknik accidental sampling. Pengolahan data menggunakan metode SEM-PLS dengan software SmartPLS 3.0. Hasil penelitian ini menunjukkan bahwa Hedonic Shopping Motivation berpengaruh terhadap Positive Emotion, Shopping Lifestyle berpengaruh terhadap Positive Emotion, Positive Emotion berpengaruh terhadap Impulse Buying, Hedonic Shopping Motivation tidak berpengaruh terhadap Impulse Buying, Shopping Lifestyle berpengaruh terhadap Impulse Buying, Hedonic Shopping Motivation memengaruhi Impulse Buying melalui Positive Emotion, dan Shopping Lifestyle memengaruhi Impulse Buying melalui Positive Emotion.